2017
DOI: 10.1038/srep38918
|View full text |Cite
|
Sign up to set email alerts
|

Discovering potential serological biomarker for chronic Hepatitis B Virus-related hepatocellular carcinoma in Chinese population by MAL-associated serum glycoproteomics analysis

Abstract: The accuracy of current biomarkers for the diagnosis of hepatocellular carcinoma (HCC), especially chronic Hepatitis B Virus (HBV)-related HCC, is limited. Recent progress in glycoproteomics has provided a novel platform for screening novel serological biomarkers of HCC. In this study, lectin affinity chromatography by Maackia amurensis lectin (MAL) and iTRAQ combined with mass spectrometric analysis were performed to enrich and identify the glycoprotein fractions in serum samples from HBV-related HCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The sensitivity and specificity of galectin-3 to predict HCC among patients with chronic viral hepatitis B were 80% and 93% respectively [27]. The present study found that galectin-3 levels were significantly higher in the HCC group than the chronic hepatitis C group without advanced fibrosis, but this cannot be helpful in clinical practice as chronic HCV patients almost always develop HCC on top of cirrhotic liver [28].…”
Section: Discussionmentioning
confidence: 52%
“…The sensitivity and specificity of galectin-3 to predict HCC among patients with chronic viral hepatitis B were 80% and 93% respectively [27]. The present study found that galectin-3 levels were significantly higher in the HCC group than the chronic hepatitis C group without advanced fibrosis, but this cannot be helpful in clinical practice as chronic HCV patients almost always develop HCC on top of cirrhotic liver [28].…”
Section: Discussionmentioning
confidence: 52%
“…Upur et al, 224 Liu et al, 225 Wang et al, 159 Hu et al, 99 Nie et al,[ 100 ] Nie et al, 67 Qin et al 101 Shetty et al 102 Tan et al 103 Ueda et al 94 Wu et al 68 Yin et al 104 Liu et al 96 and samples from Lynch syndrome and controls (n = 5). 34 As indicated previously, not all these plasma orientated studies have been direct profiling measurements.…”
Section: Ovarianmentioning
confidence: 99%
“…In the latter study ESI analysis was used to compare labeled pools from 15 subjects of each category, with validations extending to a cohort of 310 subjects. Also studying chronic Hepatitis B Virus‐related hepatocellular carcinoma (HBV‐related HCC), Liu et al used a glycoproteomic approach, indicating that Galectin 3 binding protein was a promising serum biomarker to identify HBV‐related HCC …”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that Lgals3bp expression is induced in viral infection and by many molecules that either mimic or are characteristic of ongoing inflammation and microbial infection, such as IFN-α, IFN-β, IFN-γ and TNF-α, and it has innate immune functions with special emphasis on viral and bacterial infections (Loimaranta et al, 2018). Although it was found that Lgals3bp may be a serological biomarker for acute dengue virus infection (Liu et al, 2016), acute hantavirus infection (Hepojoki et al, 2014), hepatitis C virus (HCV), human immunodeficiency virus (HIV) infection (Shaked et al, 2014;Yang et al, 2014;Rodríguez-Gallego et al, 2019), and hepatitis B virus-related hepatocellular carcinoma (Liu et al, 2017), the relationship between Lgals3bp and viral pneumonia is rarely investigated. Gpx3 protects cells and enzymes from oxidative damage (UniProt Consortium, 2015) and may be involved in immune defense against pathogenic invasion (Bathige et al, 2015).…”
Section: Discussionmentioning
confidence: 99%